From instructional design to tecnology based learning design - Yisell Góngora Parra; Olga Lidia Martínez Leyet (Ediciones Universidad de Salamanca, 2012)
Technology incorporated to education has proved to foster and improve the teaching learning process; however, in order to achieve the best results it is necessary to change traditional paradigms for the design and planning of courses and teaching materials and use technological tools with open minds and flexibility to adjust to new learning environments. This paper aims at discussing learning design, its evolution and models, referring to its origins and development as well as to pedagogical, psychological and historical tendencies that have shaped its concept. The main models are also dis-cussed, their characteristics and the learning theories that support them. Finally, this paper deals with current tendencies in learning design and its flexibility in new models and learning environments.